Clinical and epidemiological characteristics of SARS-CoV-2 virus in ambulatory children under 2 years old - Perez, Carolina A.; Ormazabal, Ivana; Pérez-Valenzuela, Javier; Araya, Andrea; Medina, Rafael A.; Perret, Cecilia (Frontiers in Pediatrics, 2022)
Background: SARS-CoV-2 is an emerging virus that has mainly affected adults; hence, most clinical information has been derived from that population. Most pediatric cases are mild and with nonspecific symptoms requiring outpatient management. Children are a major source of spread for most traditional respiratory viruses. Their role in SARS-CoV-2 transmission was thought to be relevant. Children under the age of two comprise a group that is more susceptible to infection since vaccines have not been approved for them until recently. The knowledge of clinical manifestation of COVID-19 in young children is scarce. Objectives: to describe the clinical, epidemiological, and demographic characteristics of children under 2 years old with confirmed COVID-19, who did not require hospitalization. Methods: This descriptive study was performed from May, 2020 to June, 2021. Children ages 0-2 years with COVID-19, confirmed by transcriptase-polymerase chain reaction assay that were performed in laboratories of the Red de Salud UC CHRISTUS Health Network, were selected to be contacted. If the parents accepted participating and their children were not hospitalized, a survey was sent to the patients’ caregivers. Results: Of the 242 cases, 159 caregivers answered the survey (65.7%). The median age of the subjects was 14 months, and 53.5% were males. Fifty percent had comorbidities, of which one third corresponded to atopy. Ninety eight percent were secondary cases. Most of them were infected within their households (81%). The most frequent sources were their parents, followed by their grandparents. The most common symptom was fever (78%) followed by irritability (67.3%), rhinorrhea (66%), and fatigue (64.8%). Infants less than 6 months old more often presented with conjunctival congestion and less loss of appetite compared to older children (p<0.05). Conclusions: This study provides valuable insights regarding COVID-19 in ambulatory young children. Most cases of SARS-CoV-2 infection in children under 2 years old do not require hospitalization. There was a slight male predominance, and the majority had been infected within their households. SARS-CoV-2 infection should be suspected in children under 2 years old presenting with fever, irritability, fatigue, and rhinorrhea. Children with positive household contacts and fever should also be tested for COVID-19.